1981
DOI: 10.1002/jmv.1890070304
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the liver of patients with chronic non‐A, non‐B hepatitis

Abstract: Electron microscopy examination of liver biopsies from 8 patients with chronic non-A, non-B hepatitis revealed ultrastructural changes similar to those previously described in chimpanzees with experimentally induced acute non-A, non-B hepatitis. These changes consisted of intranuclear clusters of electron-dense, 15-27-nm particles that were detected in five out of the eight patients and of circular cytoplasmic structures that were present in seven cases. Other cytoplasmic abnormalities found in our patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…The findings of the Leuven group (20), which we have confirmed, suggest that this change is associated, as it is in chimpanzees, with characteristic nuclear particles which seem not to be virus. Similar electron microscopic nuclear alterations have been found in several other studies in man (27)(28)(29)(30). The tubular cytoplasmic lesion observed in chimpanzees (3 1) has thus far been noted only by few observers (30, 32) in man.…”
Section: Discussionsupporting
confidence: 80%
“…The findings of the Leuven group (20), which we have confirmed, suggest that this change is associated, as it is in chimpanzees, with characteristic nuclear particles which seem not to be virus. Similar electron microscopic nuclear alterations have been found in several other studies in man (27)(28)(29)(30). The tubular cytoplasmic lesion observed in chimpanzees (3 1) has thus far been noted only by few observers (30, 32) in man.…”
Section: Discussionsupporting
confidence: 80%
“…The dense fused membranes may represent membrane degeneration with phospholipid accumulation. The similarity of these structures to those due to sphingomyelin accumulation in Niemann-Pick disease is very striking.4" The trilaminar tubular structures in the endoplasmic reticulum, in two of our cases, somewhat resemble structures reported in hepatocellular cytoplasm in man, chimpanzees, and tamarins.31 37 39 41-43 With no evidence of a casual role for hepatitis A or B or other viruses in the abnormal liver function tests in our patients and the absence of other factors, the possibility of NANB virus infection must be considered. Other studies have shown a high proportion of intravenous drug abusers among patients with acute NANB hepatitis admitted to an infectious disease hospital.44 In our patients the mild abnormalities of liver function tests and the similarity of the light and electron microscopic findings to those described in the NANB virus literature lend support to this suggestion.…”
Section: Discussionsupporting
confidence: 55%
“…Several ultrastructural changes in addition to those described by Shimizu et al (2) have been found associated with NANB hepatitis of chimpanzees and man, such as attaching curved membranes ( 5 , 13,14), microtubular aggregates (5), tubular fragments within the endoplasmic reticulum (15), dilatation and herniation of the endoplasmic reticulum (14,16) with lamellar inclusions (13) and crystalline arrays in liver cells ( 17) and endothelial cells (1 1, 18). None of these was a conspicuous finding in the present series of biopsies, with the exception of the wellknown lesions of the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 88%